An Improved Indoor Positioning Algorithm Based on RSSI-Trilateration Technique for Internet of Things (IOT) - Rusli M.E.; Ali M.; Jamil N.; Din M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Indoor positioning systems; Location based services; Surveying; Wireless local area networks (WLAN); Access points; Internet of Things (IOT); IOT board; Location-based applications; Positioning techniques; Received signal strength measurements; Trilateration; Wi-Fi - Technology; Internet of things